2001
DOI: 10.1177/0013161x01374003
|View full text |Cite
|
Sign up to set email alerts
|

Flukes, Opportunities, and Planned Interventions: Factors Affecting Women’s Decisions to become School Administrators

Abstract: This article presents the results of an exploratory study of women in educational administration that focused on women’s decisions to enter educational administration. Findings suggest that the career aspirations of women who ultimately enter the field of educational administration are intricately related to their career commitments, positional goals, and leadership orientations. Furthermore, although women who go into administration may have personal characteristics that set them apart from women who do not, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 22 publications
(63 reference statements)
5
69
1
Order By: Relevance
“…As such, our sample is consistent with similar research in which women tend to be much more experienced teachers than men when they assume a headship (Bell and Chase 1995;Hoff and Mitchell 2008;Young and McLeod 2001). We interviewed each woman at least twice, and the topics ranged from their biography, career trajectories and leadership practices, to their work-life balance.…”
Section: Background and Methodologysupporting
confidence: 80%
See 1 more Smart Citation
“…As such, our sample is consistent with similar research in which women tend to be much more experienced teachers than men when they assume a headship (Bell and Chase 1995;Hoff and Mitchell 2008;Young and McLeod 2001). We interviewed each woman at least twice, and the topics ranged from their biography, career trajectories and leadership practices, to their work-life balance.…”
Section: Background and Methodologysupporting
confidence: 80%
“…The latter is crucial as women are more likely to rely on affirmation than men (Hoff and Mitchell 2008). Even though the support these women received was merely 'gentle persuasion' or 'a tap on the shoulder', it could boost their confidence in their leadership ability (Young and McLeod 2001).…”
Section: Professional Encouragement and Hard Workmentioning
confidence: 99%
“…So what happened to all of those individuals who received training and licensure in educational administration? Though we do not know the exact number, we have reason to believe that in California, Texas, and a number of other states a very large number of educators with administrative credentials have remained (for whatever reason) in nonadministrative positions (Andrews & Grogan, 2001;Campbell, 2001;ERS, 1998;Glasman, Cibulka, & Ashby, 2001;Young, in press;Young & McLeod, 2001). How do we explain this apparent discrepancy?…”
Section: Educational Leadership Preparation and Practicementioning
confidence: 99%
“…As a result, many conversations and efforts have at their core negative images of traditional university preparation of school and school system leaders and the faculty who participate in such programs. Indeed it has been suggested that at the core of both the quality (i.e., preparation) and quantity (i.e., shortage) issues is the traditional university educational leadership preparation program (Young & Mcleod, 2001). While many faculty consider the negative essentializations of preparation programs (e.g., Guthrie & Sanders, 2001) to be unfair overgeneralizations, most agree that there are too many ineffective programs currently operating and thus consider much of the criticism warranted and justi®ed.…”
Section: Where Is Educational Leadership In This Conversation?mentioning
confidence: 99%
See 1 more Smart Citation